1968
DOI: 10.1104/pp.43.8.1185
|View full text |Cite
|
Sign up to set email alerts
|

The Acetylene-Ethylene Assay for N2 Fixation: Laboratory and Field Evaluation

Abstract: A bstract. The methodology, characteristics and application of the sensitive C,H.,-C2H4 assay for N2 fixation by nitrogenase preparations and bacterial cultures in the laboratory and by legumes and free-living bacteria in situ is presented in this comprehensive report. This assay is based on the N9ase-catalyzed reduction of C2Ho to C2H4, gas chromatographic isolation of C2H2 and C9H4, and quantitative measurement with a H,-fiame analyzer. As little as 1 ,u,lmole C..H4 can be detected, providing a sensitivity 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

34
1,024
7
61

Year Published

1979
1979
2014
2014

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 2,189 publications
(1,154 citation statements)
references
References 31 publications
34
1,024
7
61
Order By: Relevance
“…A atividade da enzima nitrogenase foi medida indiretamente por meio do método da atividade de redução do acetileno (ARA) (Hardy et al, 1968). Após a coleta, as raízes nodulantes foram colocadas em frascos de vidro de 1.000 mL, os quais foram fechados hermeticamente.…”
Section: Methodsunclassified
“…A atividade da enzima nitrogenase foi medida indiretamente por meio do método da atividade de redução do acetileno (ARA) (Hardy et al, 1968). Após a coleta, as raízes nodulantes foram colocadas em frascos de vidro de 1.000 mL, os quais foram fechados hermeticamente.…”
Section: Methodsunclassified
“…The total amount of nitrogen was determined colorimetrically, following the Smith method [22], after a Kjeldhahl digestion by a microwave digester Maxidigest MX350 (Prolabo, Spain). Before the plants were pressed, acetylene reduction activity (ARA) was determined in the nodule [23]. The fixed nitrogen was calculated following the method of Zhang et al [2], total plant nitrogen content minus the amount of nitrogen in the original seed (32 mg per seed, n = 25 seeds).…”
Section: Harvest and Data Collectionmentioning
confidence: 99%
“…This product profile is consistent with side-on binding of 2-butyne, with proton addition occurring at one face. Earlier work on wild-type nitrogenase revealed that proton addition to acetylene during its reduction to ethylene occurs with stereospecificity [27][28][29]. The product of acetylene (HC≡CH) reduction in the presence of D 2 O is 96 % cis-ethylene (HDC=CDH), with only 4 % of the trans-isomer [30].…”
Section: Discussionmentioning
confidence: 99%